Value based scope management of innovation projects in crisis conditions - Григорян, Тигран Георгиевич; Корзняков, Алексей Сергеевич (Technology audit and production reserves, 2015)
During the research process of value-based scope management of Innovation projects in crisis conditions it was created a system of criteria, which can be used for evaluation of the projects operations in aspect of their importance for delivering Value in the final product of the Innovation project. Thurstone method was used for the analysis of the experts’ evaluation results. It enabled to identify the most important project operations for the further redesigning of the WBS. During the crisis economic situation a manager has to keep project successful while decreasing finances. The Value-based approach was chosen for the decision making efficiency increasing. This approach allows to concentrate on choosing the most important project operations, and save the Value of the final product. A system of criteria of Innovation project success was proposed as result of the research. Also it was proposed a procedure of experts’ evaluation analyzing, which allows to range project operations for WBS redesigning. The results of the research are considered to be useful as there is an opportunity to range Innovation project operations effectively in crisis conditions.